Analysis of Factors Affecting Satisfaction to Contractors’ Performance in Retail Building Construction Work - Reinaldy Iqbal Syahdila; Rizal Bahaswan (Lembaga Penelitian dan Pengabdian Masyarakat / Narotama University Press, 2026)
The retail building construction industry has unique characteristics including tight time constraints, specific functional standards, and direct impact on business performance. This study aims to analyze factors influencing satisfaction with contractor performance in retail building construction projects, specifically focusing on Indomaret store development projects in East Java Regional I. The research employs a descriptive quantitative approach using purposive sampling of 30 respondents from five new Indomaret store construction projects. The research instrument uses the SERVQUAL model adapted for construction context with five dimensions: reliability, responsiveness, assurance, empathy, and tangibles. Results indicate very high satisfaction levels with contractor performance, with an overall average score of 4.17 or 83.4% (categorized as